TOLERANCE AS A UNIVERSAL COMPETENCE IN THE SYSTEM OF EUROPEAN EDUCATION - Yevhen Bidenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Formal and informal means are used to foster tolerance in European educational institutions, including through the establishment of a complex set of moral values (inclusion, principles of academic integrity, etc.). The declared principles are reflected in the codes of ethics, which serve as guidelines for the development of national educational systems, provide an ethical foundation for educational practices of specific universities, and so on.